Psycho-socio and Economic Factors as Determinant of Women's Academic Performance in Distance Education in South Western Nigeria - Erikitola, Joy Ozavize; Otumala, S; Oluwasola, G (Journal of Education and Practice, 2025)
Purpose: This study investigates the psycho-social and economic factors affecting the academic performance of women enrolled in distance learning programmes across South-Western Nigeria. Methodology: Using a descriptive survey design and a mixed-method approach, the study collected quantitative data from 274 valid responses out of 300 distributed questionnaires and conducted 30 Key Informant Interviews (KIIs) with academic advisors, programme coordinators, and high-performing students. Data were analyzed using t-tests, linear regression, and thematic analysis. Findings: Financial constraints, household responsibilities, workplace stress, and psychological challenges significantly influenced academic performance. Financial limitations emerged as the most significant predictor. Thematic analysis revealed four dominant themes: home-front pressures, financial constraints, workplace stress, and psychological impacts. Unique Contribution to Theory, Policy and Practice: The study advances understanding of gender-specific barriers in distance education. It recommends institutional reforms such as flexible learning schedules, targeted student support services, and expanded financial aid. Policy implications include enhancing workplace flexibility, subsidized childcare, and promoting family and community-based academic support systems for women.